Unlocking the mystery of manufacturing SMEs' performance by utilizing the power of strategic innovation - AlQershi, Nagwan; Abas, Zakaria; Mohd Mokhtar, Sany Sanuri (School of Technology Management and Logistics (STML), 2019)
In the context of developing nations, Small and Medium Enterprises (SMEs) make significant contributions to economic development (Isaga, Masurel, & Van Montfort, 2015; Abor & Quartey, 2010; Kapurubandara & Lawson, 2006). Many nations have targeted the development of the SME sub-sector as a major part of their overall economic plans (Khalique, Bontis, Abdul Nassir, & Hassan, 2015). In general, SMEs around the world have a key role in the growth and sustainability of the economy (Kaur & Sharma, 2016). In this regard, organizations that enjoy a competitive edge are more likely to achieve high value and optimum performance, as revealed by Barney (1991). Over the years, the role of competitive advantage in improving the performance of business organizations has been comprehensively scrutinized (e.g., Albrecht, Bakker, Gruman, Macey & Saks, 2015; Asmussen & Foss, 2014). Organizations have to shift from technology-oriented entities into ones that thrive on strategic innovation (Shams, Vrontis, Weber & Tsoukatos, 2018).